Error Analysis In Writing Descriptive Text In The First Semester Of Social Science Students Of STKIP Al Maksum - yusrah; Syafii (The Seall Journal, 2021)
Writing as a productive skill is important for students to express their ideas. However, students conducted errors in the productive skills. Therefore, this study is intended to find out types of errors made by students in written English. This study employed the qualitative method where the Error Analysis was implemented. The subject of this study is students in first First Semester of Social Science Students of Al Maksum and the object of this study were the errors found in written English. The population of this research was all of students in first semester which consists of 90 students from all study programs where 25 % of the populations were taken as the sample. To collect the data, written tests were conducted. The written test shows the percentage of writing errors, including omission errors, which is 58.38%, misformation errors with a total of 16.48%, misordering error 13.89%, and addition of 11.26%. The errors were found when students omitted 'to be' as main verb. Second, students tend to add 'to' after modal auxiliaries such as 'can' or 'will'. Third, misformation errors happened when students could not form the verb correctly. Last, the misordering errors were produced when students put words randomly. Consequently, it was discovered that the errors made by students were impacted by their native language, and this is the interlanguage Keywords: error analysis, Surface Structure Taxonomy, writing.